Protein kinase C and P2Y12 take center stage in thrombin‐mediated activation of mammalian target of rapamycin complex 1 in human platelets. (May 2014) - Moore, S. F.; Hunter, R. W.; Hers, I.
Summary Background Rapamycin, an inhibitor of mammalian target of rapamycin complex‐1 (mTORC1), reduces platelet spreading, thrombus stability, and clot retraction. Despite an important role of mTORC1 in platelet function, little is known about how it is regulated. The objective of this study was to determine the signaling pathways that regulate mTORC1 in human platelets. Methods Mammalian target of rapamycin complex‐1 activation was assessed by measuring the phosphorylation of its downstream substrate ribosomal S6 kinase 1 (p70S6K). Results Thrombin or the protein kinase C (PKC) activator phorbal 12‐myristate 13‐acetate stimulated activation of mTORC1 in a PKC‐dependent, Akt‐independent manner that correlated with phosphorylation of tuberin/tuberous sclerosis 2 (TSC2) (Ser939 and Thr1462). In contrast, insulin‐like growth factor 1 (IGF‐1)–stimulated TSC2 phosphorylation was completely dependent on phosphoinositide 3 kinase (PI3 kinase)/Akt but did not result in any detectable mTORC1 activation. Early (Ser939 and Thr1462) and late (Thr1462) TSC2 phosphorylation in response to thrombin were directly PKC dependent, whereas later TSC2 (Ser939) and p70S6K phosphorylation were largely dependent on paracrine signaling through P2Y12. PKC‐mediated adenosine diphosphate (ADP) secretion was essential for thrombin‐stimulated mTORC1 activation, as (i) ADP rescued p70S6K phosphorylation in the presence of a PKC inhibitor and (ii) P2Y12 antagonism prevented thrombin‐mediated mTORC1 activation. Rescue of mTORC1 activation with exogenous ADP was completely dependent on the Src family kinases but independent of PI3 kinase/Akt. Interestingly, although inhibition of Src blocked the ADP rescue, it had little effect on thrombin‐stimulated p70S6K phosphorylation under conditions where PKC was not inhibited. Conclusion These results demonstrate that thrombin activates the mTORC1 pathway in human platelets through PKC‐mediated ADP secretion and subsequent activation of P2Y12, in a manner largely independent of the canonical PI3 kinase/Akt pathway.